1981
DOI: 10.1042/cs0610429
|View full text |Cite
|
Sign up to set email alerts
|

Methods to Assess Breathlessness in Healthy Subjects: A Critical Evaluation and Application to Analyse the Acute Effects of Diazepam and Promethazine on Breathlessness Induced by Exercise or by Exposure to Raised Levels of Carbon Dioxide

Abstract: 1. Methods were devised and evaluated for inducing breathlessness by submaximal graded exercise in healthy subjects while objective measurements of cardiorespiratory function were made. Breathlessness was assessed with serial visual analogue scales (VAS), but with various measures to enhance repeatability. 2. A high level of reproducibility was obtained in spite of the subjective nature of the assessment. Individual responses were described by the relationship between breathlessness and ventilation. The sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
2
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(45 citation statements)
references
References 0 publications
2
40
2
1
Order By: Relevance
“…The test was similar to that described in detail previously (Stark et al, 1981). Sub-maximal exercise was undertaken by walking on an inclined treadmill at three speeds (2 kph for 2 min, 4 kph for 2 min and 6 kph for 2 min) to achieve a range of values for ventilation rather than a steady state.…”
Section: Exercise Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The test was similar to that described in detail previously (Stark et al, 1981). Sub-maximal exercise was undertaken by walking on an inclined treadmill at three speeds (2 kph for 2 min, 4 kph for 2 min and 6 kph for 2 min) to achieve a range of values for ventilation rather than a steady state.…”
Section: Exercise Testmentioning
confidence: 99%
“…The latter was assessed using methods we have described and validated (Stark et al, 1981(Stark et al, , 1983a). …”
Section: Introductionmentioning
confidence: 99%
“…The test was similar to that described in detail previously (Stark et al, 1981). In brief, submaximal exercise was undertaken on a treadmill to achieve a range of values of minute ventilation and breathlessness was assessed with visual analogue scales (VAS) at intervals of 1 min.…”
Section: Exercise Testmentioning
confidence: 99%
“…MitchellHeggs et al (1980) reported that diazepam reduced dyspnoea in patients with the 'pink puffer' syndrome but the larger study of Woodcock et al (1981) failed to confirm this effect in similar patients. Any benefit of diazepam might be secondary to sedation and for this reason Stark et al (1981), in their investigation in healthy subjects, included promethazine as a control treatment. Surprisingly, breathlessness during exercise was reduced but this effect did not achieve statistical significance.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to CO 2 stimulates respiration and pigs start to hyperventilate (Raj and Gregory, 1996). In humans, this is described as breathlessness which is known to increase with blood carbon dioxide levels (Stark et al, 1981). Moreover, CO 2 is an acidic gas with a high solubility that together with water forms carbonic acid.…”
Section: Dotted Lines Indicate Average Values Of All Observations Amentioning
confidence: 99%